Isothermal and non-isothermal oxidation kinetics of nanooxide dispersed high Cr ferritic steel prepared by mechanical alloying. (1st September 2013) - Karak, S K; Dutta Majumdar, J; Manna, I
Abstract : Oxidation kinetics based on Kissinger-Akahira-Sunose analysis of high Cr ferritic steel synthesised by mechanical alloying of elemental powder blend of 84Fe-13·5Cr-2·0Al with 0·5 nano-Y2 O3 (all in wt-%) dispersion followed by cold compaction with 250 MPa pressure and sintering in vacuum (10 −6 mbar) at 1000°C for 1 h have been investigated under isothermal (600-900°C for up to 50 h) and non-isothermal conditions (50-1200°C with heating rates of 10, 20, 30 or 40°C min −1 ). Mechanism of oxidation was taken place by counterionic transport of oxygen from surface to interior and cations (Cr 3+ /Fe 3+ ) from the interior to the surface through grain boundary at low oxidation temperature (∼600°C) and through grains at high oxidation temperature (700-900°C). Early formation of Cr rich spinel layers on the surface improves the oxidation resistance by acting as the diffusion barrier against counterionic transport of ions during oxidation.